Writers Are Common among Parkinson’s Disease Patients: A Longitudinal Study - Anna Aasly; Jan O. Aasly (Behavioural Neurology)
Parkinson’s disease (PD) patients may have a specific personality profile, which includes being introvert, cautious and devoted to hard work. The evaluation of psychological characteristics must be evaluated according to methods for assessments of personality disorders. Such evaluations are often time-consuming and available only in research settings. The “parkinsonian trait” may be established early in life but may change with disease progression. To overcome this long interval before onset of PD questions on literary activities were included in the medical record. Three percent of PD patients could be defined as writers, significantly higher than observed in the general population. PD writers published their first books long before onset of disease. Being a writer is an extrovert trait meaning that the patient is prepared for criticism and publicity. We suggest that questions regarding personal activities prior to disease onset add valuable information on personality which differs significantly from traits observed later in the disease period.